Patterns and perceptions of vaping among adults living in social housing: a representative survey in Great Britain, 2023 - Sarah E Jackson; Jamie Brown; Dan Lewer; Sharon Cox (BMC, 2024)
Abstract Background Vaping products are effective for helping people to stop smoking and may therefore offer a potential means to reduce high rates of smoking in socioeconomically disadvantaged groups. This study aimed to examine current patterns and perceptions of vaping among people living in social housing in Great Britain compared with those living in other housing types. Methods Data were from the Smoking Toolkit Study; a nationally-representative survey conducted in 2023 (n = 23,245). Logistic regression tested cross-sectional associations between living in social (vs. other) housing and current vaping among adults; vaping frequency, device type, nicotine concentration, and source of purchase among current vapers; use of vaping products as a smoking cessation aid among past-year smokers who tried to quit; and harm perceptions of vaping products relative to cigarettes among current smokers. Results Current vaping prevalence was twice as high among adults living in social housing (19.4%) compared with those in other housing types (10.4%; OR = 2.07, 95%CI = 1.84-2.33). This was partly explained by differences in sociodemographic characteristics and smoking status; after adjustment, the odds of being a current vaper were 33% higher (ORadj=1.33, 95%CI = 1.14-1.54). Among vapers, there were no notable differences by housing tenure in vaping frequency, main device type used, usual nicotine concentration, usual source of purchase, or use as a smoking cessation aid. However, current smokers living in social housing were more likely to think vaping is more harmful than cigarettes (31.6% vs. 21.8%; ORadj=1.61, 95%CI = 1.30-1.99). Conclusions In Great Britain, adults who live in social housing are more likely to vape than those who live in other housing types, even after accounting for their younger age and higher smoking rates. However, misperceptions about the relative harms of vaping products and tobacco are common among smokers living in social housing. Interventions addressing these misperceptions could help encourage more people living in social housing to switch from smoking to vaping and reduce smoking-related health inequalities. Pre-registration The study protocol and analysis plan were pre-registered on Open Science Framework (https://osf.io/n3mvs/).